Managing the unknown or the art of preventing SARS-CoV-2 infection in workplaces in a context of evolving science, precarious employment, and communication barriers. A qualitative situational analysis in Quebec and Ontario - Côté, Daniel; MacEachen, Ellen; Huynh, Ai-Thuy; León, Amelia; Laberge, Marie; Meyer, Samantha; Majowicz, Shannon; Amoako, Joyceline; Jahangir, Yamin; Dubé, Jessica (Frontiers in Public Health, 2024)
Introduction The issue of communications in the public space, and in particular, in the workplace, became critical in the early stages of the SARS-CoV-2 pandemic and was exacerbated by the stress of the drastic transformation of the organization of work, the speed with which new information was being made available, and the constant fear of being infected or developing a more severe or even fatal form of the disease. Although effective communication is the key to fighting a pandemic, some business sectors were more vulnerable and affected than others, and the individuals in particular socio-demographic and economic categories were proportionately more affected by the number of infections and hospitalizations, and by the number of deaths. Therefore, the aim of this article is to present data related to issues faced by essential workers interacting with the public and their employers to mitigate the contagion of SARS-CoV-2 (COVID-19) at work. Methods Following the constructivist paradigm, an interpretative qualitative design was used to conduct one-on-one interviews with precarious/low-wage, public-contact workers (N = 40), managers (N = 16), and key informants (N = 16) on topics related to their work environments in the context of COVID-19 prevention. Results This article has highlighted some aspects of communication in the workplace essential to preventing COVID-19 outbreaks (e.g., access to information in a context of fast-changing instructions, language proficiency, transparency and confidentiality in the workplace, access to clear guidelines). The impact of poor pre-pandemic working relations on crisis management in the workplace also emerged. Discussion This study reminds us of the need to develop targeted, tailored messages that, while not providing all the answers, maintain dialog and transparency in workplaces.